The effects of education on access to financial institutions - Castillo, Jad Algin Salamat (School of Economics, University of the Philippines Diliman, 2019)
Education is one of the primary goals of the Philippines, under the Philippine Development Plan 2017_2022, along with an inclusive monetary and financial system by the Bangko Sentral ng Pilipinas. Part of creating an inclusive financial system is through financial literacy. It is important for people to be knowledgeable about financial products and services for various reasons that can improve their welfare. Our research aims to study the effects of education to access to financial institutions of households in the Philippines using probabilistic regression and multinomial probit models of the 2017 Financial Inclusion Survey by the BSP. We used marginal effects of educational attainment to measure its partial effects relative to other socioeconomic and demographic factors. To further establish the relationship, we did specification tests by measuring financial institutions based on its formal and informal types, and by using different income variables of households. As a result, increases to educational attainment positively affects access to financial institutions; however, with low levels of education only to informal institutions. The findings also suggested that other household factors have positive effect on access to financial institutions such as income, age, urban areas, and employment and negative effect for regional area.